THEORETICAL ASPECTS OF DETERMINING AND FORMATION OF FUTURE SPECIALISTS’ IN PHYSICAL REHABILITATION PROFESSIONAL IDENTITY - Копочинська, Ю. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The article analyzes theoretical aspects of professional identity and its formation in a higher educational institution, considers professional identity as the main concept reflecting the essence of professional development of specialists in physical rehabilitation. The applied significance of these issues is exacerbated in the case of the need to determine the criteria for effective professional implementation of professionals working in the field of human-to-human relations